Trade Policy, Cumulative Causation, and Industrial Development. - Venables, A (1996)
This paper considers the effects of trade policy in industries which are imperfectly competitive, and in which there is an input-output structure, creating vertical linkages between firms. Two models are presented, one based on Cournot oligopoly and the other on Dixit-Stiglitz product differentiation. In both models it may be the case that trade liberalization triggers a dramatic expansion of output and possibly also a reduction in imports. This arises as import liberalization lowers costs in downstream industries, expanding their output, and triggering a 'big push' of industrialization.